Recent trends in spin-resolved photoelectron spectroscopy. (13th November 2017) - Okuda, Taichi
Abstract: Since the discovery of the Rashba effect on crystal surfaces and also the discovery of topological insulators, spin- and angle-resolved photoelectron spectroscopy (SARPES) has become more and more important, as the technique can measure directly the electronic band structure of materials with spin resolution. In the same way that the discovery of high-Tc superconductors promoted the development of high-resolution angle-resolved photoelectron spectroscopy, the discovery of this new class of materials has stimulated the development of new SARPES apparatus with new functions and higher resolution, such as spin vector analysis, ten times higher energy and angular resolution than conventional SARPES, multichannel spin detection, and so on. In addition, the utilization of vacuum ultra violet lasers also opens a pathway to the realization of novel SARPES measurements. In this review, such recent trends in SARPES techniques and measurements will be overviewed.